Considerations about destructive behaviour reasonable features - Vardanyan, Kamo (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The article discusses various manifestations, mechanisms, and patterns of self-destructive behavior. A special methodology for studying suicides is offered. Suicide research requires additional training for a psychologist because it is a unique 71 field of psychology where there is a process of fixing destructive information and destructive infection. The interpretation of criminal cases attempts to present the peculiarities of selfdestructive and suicidal behavior of juveniles, gamblers, convicts in penitentiaries, and people suffering from post-traumatic stress disorder. Every suicide has its specific reason, certain condition, and occasion. The reasons for suicide are various and very unique, but at the core of it, all are the processes of disinfection.